Thomas, Margaret (London, 2013)
2013 "Thomas, Margaret", 2013, HistoryTalk Margaret Thomas left school in her native Scotland and worked in various departments of the Civil Service: initially the Ministry of Defence and then the Department of Agriculture and Fisheries, before moving to London to re-join her first employer. Thereafter, she worked for several years at British European Airways West London Air Terminal, having joined in 1967, and then worked for BEAs in-bound travel service, Windsor Tours, eventually leaving in 1979 to have a baby. Having initially returned to employment after a 6 year break bringing up her son, by working for a term as a classroom assistant in a Primary School, Margaret worked as an Examinations Officer at The Poetry Society for nine years; performing the same role at the Central School of Speech and Drama for a further two years, when the scheme was taken under its auspices. Finally, Margaret worked for many years, undertaking a variety of roles, for the General Dental Council, until taking her retirement. Margaret has lived for most of her working life in West London.